Needs of home hospice palliative care patients in terms of functional impairment and physiotherapy options - Bąk, Małgorzata (Medycyna Paliatywna/Palliative Medicine, 2025)
As cancer progresses, patients experience multiple complaints in all areas of their life and withdraw from full life activity. The home hospice often remains the only form of support and assistance, and physiotherapy is seen as an indispensable part of the patient’s overall palliative management. In an effort to improve the patient’s real situation and, thus, his/her quality of life, it is important to listen to the patient’s opinion, needs and expectations. Such an approach aims at the subjective treatment of the patient and his or her problems. The physiotherapist’s action must be based on partnership, humanisation and individualisation. It is very important that the physiotherapy plan is adapted to each phase of the disease. At the same time it necessary to short-term and long-term goals of action. The demand for physiotherapists working with patients at home has been increasing for several years, and along with it, expectations towards physiotherapists are also growing.